Sir Fred in the Windy City The Joffrey Ballet's Ashton revivals - Brooks, Bonnie (Dance Books Ltd., Alton,Hampshire (UK), 2004)
The Joffrey Ballet's Ashton revivals. Les Patineurs, a deceptively complicated ensemple romp on faux ice, is an example of Ashton's ability to convey emotional content and social commentary by way of movement. PALABRAS CLAVE: Joffrey Ballet, Frederick Ashton, Gerald Arpino, Les Patineurs, Monotones I &II, A Wedding Bouquet.